Dynamic performance of detuned ridge waveguide AlInGaAs distributed feedback laser diodes. Issue 6 (30th March 2017) - Cantú, H.I.; McKee, A.; Childs, D.; Watson, S.; Kelly, A.E.
ABSTRACT: The dynamic behavior of AlInGaAs ridge waveguide distributed feedback lasers is reported in this work covering five detuned wavelengths between 1291 nm and 1326 nm for a laser active layer optical peak gain design centered at 1310 nm at room temperature. The detuning is achieved by modifying the laser grating pitch that performs the mode selection within the laser cavity simultaneously across a single processed wafer. The dynamic behavior is evaluated using the resonance frequencies of the detuned lasers measured at a range of injection currents for heatsink temperatures of 25°C and 85°C. The results confirm that a speed improvement can be achieved at 25°C by detuning the laser to shorter wavelengths. However, the results also show that a lower direct modulation bandwidth at 85°C makes the shorter wavelength design less attractive. For communications applications such as 10 Gbps uncooled operation, this trade‐off between detuning and modulation bandwidth imply an optimum around −2 nm to +8 nm detuning (measured at 25°C). © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:1468–1470, 2017